Cross-Reactivity to Mutated Viral Immune Targets Can Influence CD8+ T Cell Functionality: An Alternative Viral Adaptation Strategy - Currenti, Jennifer; Law, Becker M.P.; Qin, Kai; John, Mina; Pilkinton, Mark A.; Bansal, Anju; Leary, Shay; Ram, Ramesh; Chopra, Abha; Gangula, Rama; Yue, Ling; Warren, Christian; et al. (Frontiers in Immunology, 2021)
Loss of T cell immunogenicity due to mutations in virally encoded epitopes is a well-described adaptation strategy to limit host anti-viral immunity. Another described, but less understood, adaptation strategy involves the selection of mutations within epitopes that retain immune recognition, suggesting a benefit for the virus despite continued immune pressure (termed non-classical adaptation). To understand this adaptation strategy, we utilized a single cell transcriptomic approach to identify features of the HIV-specific CD8+ T cell responses targeting non-adapted (NAE) and adapted (AE) forms of epitopes containing a non-classical adaptation. T cell receptor (TCR) repertoire and transcriptome were obtained from antigen-specific CD8+ T cells of chronic (n=7) and acute (n=4) HIV-infected subjects identified by either HLA class I tetramers or upregulation of activation markers following peptide stimulation. CD8+ T cells were predominantly dual tetramer+, confirming a large proportion of cross-reactive TCR clonotypes capable of recognizing the NAE and AE form. However, single-reactive CD8+ T cells were identified in acute HIV-infected subjects only, providing the potential for the selection of T cell clones over time. The transcriptomic profile of CD8+ T cells was dependent on the autologous virus: subjects whose virus encoded the NAE form of the epitope (and who transitioned to the AE form at a later timepoint) exhibited an ‘effective’ immune response, as indicated by expression of transcripts associated with polyfunctionality, cytotoxicity and apoptosis (largely driven by the genes GZMB, IFNɣ, CCL3, CCL4 and CCL5). These data suggest that viral adaptation at a single amino acid residue can provide an alternative strategy for viral survival by modulating the transcriptome of CD8+ T cells and potentially selecting for less effective T cell clones from the acute to chronic phase.